Pengaruh Penggunaan Media Audiovisual Oleh Guru Seni Budaya dalam Meningkatkan Motivasi Belajar Siswa Kelas X SMA Negeri 1 Adiankoting - Dinda Anjelika Manik (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The aim of this research is to determine the positive and significant influence of the use of audiovisual media by arts and culture teachers in increasing the learning motivation of class X students at SMA Negeri 1 Adiankoting. The method used in this research uses a quantitative approach. The population, namely all class Data was collected using a positive closed questionnaire with 40 items. The results of data analysis show that there is a positive and significant use of audiovisual media by arts and culture teachers in increasing the learning motivation of class ttable(a=0.05,dk=n-2=60)= 2,000, thus there is a significant relationship between variable b) Regression coefficient of determination test (r2) = 25.8%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=24, dk denominator=n-2=62-2=60) namely 20.85 > 1.39. Thus, Ha, namely that there is a positive and significant influence on the use of audiovisual media by arts and culture teachers in increasing the learning motivation of class X students at SMA Negeri 1 Adiankoting, is accepted and H0 is rejected.